1972
DOI: 10.1159/000136269
|View full text |Cite
|
Sign up to set email alerts
|

Kinins – Evidence for the Involvement in Lymphostatic Encephalopathy in Rats

Abstract: Five days after blockade of the cervical lymph vessels rats suffer from lymphostatic encephalopathy with impaired central nervous function and cerebral edema. The vascular permeability in the brain for i.v. injected Evans blue is increased. The enhancement of the permeability is suppressed after depletion of kininogen with hog pancreatic kallikrein and cellulose sulphate or by increase of the kinin destroying enzymes (carboxypeptidase B). Trasylol® and SBTI have no effect. Kinins are shown to play a role in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1973
1973
1980
1980

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Jod et al (1969) andVarkonyi et al (1969) thought that an increased extravasation of Evans blue into brain tissue of lymphostatic encephalopathic rats points at a general increase in blood-brain barrier permeability. Firstly, this view was supported by Wendel and Seidel (1972) when they, too, found an increased Evans blue content of the brains of lymphostatic encephalopathic rats. However, later on Seidel (1972) demonstrated that after perfusing the brains in situ with 0.9 % NaCl in lymphostatic encephalopathic and sham-operated rats the cerebral dye contents were no longer different.…”
Section: Discussionmentioning
confidence: 90%
“…Jod et al (1969) andVarkonyi et al (1969) thought that an increased extravasation of Evans blue into brain tissue of lymphostatic encephalopathic rats points at a general increase in blood-brain barrier permeability. Firstly, this view was supported by Wendel and Seidel (1972) when they, too, found an increased Evans blue content of the brains of lymphostatic encephalopathic rats. However, later on Seidel (1972) demonstrated that after perfusing the brains in situ with 0.9 % NaCl in lymphostatic encephalopathic and sham-operated rats the cerebral dye contents were no longer different.…”
Section: Discussionmentioning
confidence: 90%
“…Brains were removed and cut carefully into halves. After weighing the two hemispheres separately, Evans blue concentration of brain substances was estimated as described by W endel and Seidel [21]. Group 1.2 (cortical freezing; benzopyrone treatment; n = 15).…”
Section: Group 11 (Cortical Freezing; Saline Treatment; N = 16)mentioning
confidence: 99%
“…Die EvansBlau-Fluoreszens-Methode zeigte auf lichtmikroskopischem Wege das Ein dringen des Farbstoffes tief in normalerweise von der Blut-Hirn-Schranke geschützte Hirngebiete [15]. W endel und Seidel wiesen, im Zustand der lymphostatischen Enzephalopathie, auf biochemischem Wege eine erhöhte Evans-Blau-Aufnahme der Hirnsubstanz nach [16]. …”
Section: Gruppeunclassified